2010
DOI: 10.1108/00070701011034385
|View full text |Cite
|
Sign up to set email alerts
|

Potential cross‐contamination of the ready‐to‐eat dried meat product, biltong

Abstract: PurposeThe aim of this paper is to evaluate the hygiene of surfaces that come into direct contact with the ready to eat dried meat product, biltong, at point‐of‐sale in three different retailers in Johannesburg, South Africa, by investigating the presence of indicator organisms.Design/methodology/approachSamples were collected and plated in duplicate for aerobic plate, total Enterobacteriaceae, coliforms and Escherichia coli counts using standard methods. Typical E. coli colonies on Rapid E. coli 2 Agar™ were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 28 publications
4
13
1
1
Order By: Relevance
“…In this sense, improving cleaning and disinfection procedures through hand washing, changing of gloves, and daily sanitation of cutting utensils and display cabinets is essential (Naidoo & Lindsay, 2010).…”
Section: Biofilm Formation and Food Contact Surfacesmentioning
confidence: 99%
“…In this sense, improving cleaning and disinfection procedures through hand washing, changing of gloves, and daily sanitation of cutting utensils and display cabinets is essential (Naidoo & Lindsay, 2010).…”
Section: Biofilm Formation and Food Contact Surfacesmentioning
confidence: 99%
“…However, there has been concerns about its microbial profile. Studies assessed the levels of organisms that are naturally present in a variety of biltong that was bought from various stores throughout South Africa ( Van der Riet, 1976a;Wolter et al, 2000;Mhlambi et al, 2010;Naidoo & Lindsay, 2010c;Naidoo & Lindsay, 2010a;Petit et al, 2014) and Botswana (Matsheka et al, 2010). Burfoot et al (2010) compiled a summary of results, which concluded that commercial biltong has total viable counts up to 7 log cfu/g, Enterobacteriaceae and coliforms up to 4 log cfu/g, yeasts up to 7 log cfu/g, moulds up to 5 log cfu/g, lactic acid bacteria up to 8 log cfu/g, and Staphylococci up to 8.5 log cfu/g.…”
Section: Microbial Quality and Shelf-life Of Biltongmentioning
confidence: 99%
“…The overall quality of biltong processed under both the convective and infrared conditions in the present study was therefore satisfactory in terms of the heterotrophic microbial load in comparison with recommended guideline data (Table 3). However, these results do not take into account the potential post-production contamination of biltong occurring when such food material is exposed to poor hygiene conditions as highlighted in a study by Naidoo and Lindsay (2010b). …”
Section: Discussionmentioning
confidence: 89%
“…Some of the dried ready-to-eat (RTE) meat products produced across the world include: Brazilian Charque , Ethiopian Qwanta , American Jerky , Canadian Pemmican and Tunisian Kaddid (Heinz and Hautzinger, 2010; Norman and Corte, 1985; Naidoo and Lindsay, 2010a, 2010b). Biltong is a popular meat-based RTE snack widely consumed in South Africa, which is commonly described in the country as a national delicacy (Naidoo and Lindsay, 2010b). Although limited information is available about the size of the South African biltong market, it was estimated that at least 100 tons of biltong were produced annually by 1984 (Osterhoff and Leistner, 1984).…”
Section: Introductionmentioning
confidence: 99%